Strategi Komunikasi Pengurus dalam Memakmurkan Mushala Nurul Huda Jorong Guguak Nagari Sungai Beringin - Khairini Khairini; Fajri Ahmad (Lembaga Yasin AlSys, 2026)
Although communication strategies for promoting the vitality of mushallas have received attention in several previous studies, research specifically examining their application in mushallas with low levels of congregational participation remains limited. This study aimed to analyze the communication strategies implemented by the administrators of Mushalla Nurul Huda Jorong Guguak Nagari Sungai Beringin in promoting the vitality of the mushalla and to identify the challenges encountered. This study used a qualitative approach with a case study design. The research informants consisted of mushalla administrators and the mushalla imam, who were selected using purposive sampling. Data were collected through observation, interviews, and documentation, and then analyzed using interactive analysis techniques. The results showed that the communication strategies implemented included audience identification, message formulation, method determination, and the use of communication media. However, these strategies remained conventional and had not optimally utilized digital technology. The main challenges identified included internal factors, namely limited human resources and funding, as well as external factors, namely community members’ busy schedules and the low utilization of technology. These findings contribute to the development of studies on communication strategies in the context of community-based da'wah and broaden understanding of communication dynamics in promoting the vitality of mushallas. The conclusion of this study emphasizes the importance of communication innovation and the use of technology to increase congregational participation, while also recommending that mushalla administrators develop more adaptive communication strategies. The implications of this study include theoretical contributions to the literature on da'wah communication and practical implications for mushalla management at the local level, particularly in strengthening congregational participation through contextual and responsive communication approaches.